THE ROLE OF ORGANIZATIONAL POLITICS IN THE RELATIONSHIP OF PARTICIPATIVE BUDGETING WITH BUDGETARY SLACK AND PERFORMANCE BASED BUDGETING - Kurnianto, Sigit; Rita Sulistyawati (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
The aim of this study is to examine the effect of Participative Budgeting on Budgetary Slack with Organizational Politics as a moderating variable in the public sector; examine the effect of Budgetary Slack on Performance Based Budgeting. This study examines data using a causal model with Partial Least Square (PLS) statistical analysis tools. The data used in this study are primary data from all Regional Apparatus Organizations (OPD) in Banyuwangi Regency involved in the local government budget process. Population screening based on the criteria set so that there are 64 samples of respondents involved in the budgeting process of local government organizations in Banyuwangi. The results showed that Participative Budgeting has no effect on Budgetary Slack; Organizational politics as a moderator predictor that has a positive effect on the relationship between participative budgeting and Budgetary Slack; There is no significant relationship between Budgetary Slack and Performance Based Budgeting. The research results are expected to be a development of literature and accounting studies in the field of government budgeting. Practically, the results of the study can be used as a reference for better budgeting so as to create an effective, efficient, and economical b udget and can reduce the slack that occurs.